2007
DOI: 10.1016/j.respol.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading the technological capabilities of foreign transnational subsidiaries in developing countries: The case of electronics in Thailand

Abstract: Although substantial research shows the importance of transnational corporations (TNCs) to export led growth in some developing countries, it cannot be assumed that TNC subsidiaries will automatically upgrade their capabilities through time or in a uniform fashion. This paper explores the pattern and pace of a sample of exporting TNC subsidiaries operating in the electronics industry in Thailand. The analysis reveals a wide variety in capability building approaches through time, with some subsidiaries failing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 24 publications
3
75
0
2
Order By: Relevance
“…They found that these relationships help exporters in developing countries to lower entry costs and act as instruments for information, technology diffusion and access to industrial networks. Hobday and Rush (2007) analysed the role of FDI in building export capabilities of subsidiaries in Thailand. They found that some subsidiaries upgraded capabilities while others remained as assembling plants.…”
Section: Fdi and Global Engagementmentioning
confidence: 99%
“…They found that these relationships help exporters in developing countries to lower entry costs and act as instruments for information, technology diffusion and access to industrial networks. Hobday and Rush (2007) analysed the role of FDI in building export capabilities of subsidiaries in Thailand. They found that some subsidiaries upgraded capabilities while others remained as assembling plants.…”
Section: Fdi and Global Engagementmentioning
confidence: 99%
“…Therefore, this paper uses a different perspective. The framework used by the authors to understand the technological trajectory performed by Iguaçu is similar to other studies in emerging economies of different industries such as Software (Rousseva, 2008), LCD-LED (Xie and Wu, 2003;Xie, 2004;Chuang, 2008), communications (Marcelle, 2005), electronics (Kim, 1997;Ariffin and Bell, 1999;Ariffin and Figueiredo, 2004;Hobday and Rush, 2007;and others), manufacture (Karaoz and Albeni, 2005;Chen, 2009;Nan, 2011 and others). All this studies focus high technologybased industries, and the international literature presents scarcity of empirical evidence in low-medium technologybased industries.…”
Section: Introductionmentioning
confidence: 74%
“…Kim (1997) describes technological capacity as the ability to make effective use of technological knowledge in an effort to assimilate, use, adapt and change existing technologies, with the resulting expectations of technological developments, new products and processes to respond the changes in the economic environment. Meanwhile, Hobday & Rush (2007) define it as knowledge, skills and organizational skills accumulated, which enable the company to acquire, develop and use technology to achieve competitive advantage. Both definitions refer to the importance of using knowledge as a central element of technological capability.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Basant & Chandra (2002) examine the technological capabilities of the manufacturing industry in India, finding that companies use value chains to develop products and process technology. Hobday & Rush (2007) have researched the improvement of technological capabilities in transnational corporations in developing countries, such as Thailand, in particular software companies. Hobday and Rush explain that a major factor in local capability development was the TNC's overall corporate strategy and, in particular, the way in which Thai subsidiaries fitted into global division of corporate.…”
Section: Introductionmentioning
confidence: 99%